A Case Study of Suspected Pseudomonas putida Infection in Macaca fascicularis by Histopatholohical Analysis of the Organs of Lungs, Liver, Spleen, and Kidneys (Indonesian Journal of Primatology, 2025)
Pseudomonas putida is a gram-negative, rod-shaped, flagellated bacterium that found in soil and water habitats where there is oxygen. The bacteria was obtained through bacteria culture from organs swab of Cynomolgus monkey, Macaca fascicularis. This study aims to evaluate and analyse the histological slides of Macaca fascicularis organs including the liver, kidneys, lungs, and spleen that are suspected of Pseudomonas putida infection,. The most common lesion found is cell necrosis which can be seen in lungs, liver and spleen samples. Another lesion that can be found in liver, lungs and kidneys are congestion around the cells, whereas haemorrhages can be found in red pulp and capsules of the spleen as well as the tubules of kidneys. Abundant inflammatory cells can be found in all the organ sample, such as liver, lungs, spleen and kidneys as all the organs are infected with the bacteria. The last lesion that can be found in lungs sample is benign pulmonary nodules. Based on the histopathological analysis, we can conclude that the most affected organs caused by P. putida infection is the lungs whereas the least affected organs by P. putida are the kidneys.